Age-Related Mitochondrial Impairment and Renal Injury Is Ameliorated by Sulforaphane via Activation of Transcription Factor NRF2 - Razia Sultana Mohammad; Mustafa F. Lokhandwala; Anees A. Banday (MDPI AG, 2022)
Age is one of the major risk factors for the development of chronic pathologies, including kidney diseases. Oxidative stress and mitochondrial dysfunction play a pathogenic role in aging kidney disease. Transcription factor NRF2, a master regulator of redox homeostasis, is altered during aging, but the exact implications of altered NRF2 signaling on age-related renal mitochondrial impairment are not yet clear. Herein, we investigated the role of sulforaphane, a well-known NRF2 activator, on age-related mitochondrial and kidney dysfunction. Young (2-4 month) and aged (20-24 month) male Fischer 344 rats were treated with sulforaphane (15 mg/kg body wt/day) in drinking water for four weeks. We observed significant impairment in renal cortical mitochondrial function along with perturbed redox homeostasis, decreased kidney function and marked impairment in NRF2 signaling in aged Fischer 344 rats. Sulforaphane significantly improved mitochondrial function and ameliorated kidney injury by increasing cortical NRF2 expression and activity and decreasing protein expression of KEAP1, an NRF2 repressor. Sulforaphane treatment did not affect the renal NRF2 expression or activity and mitochondrial function in young rats. Taken together, our results provide novel insights into the protective role of the NRF2 pathway in kidneys during aging and highlight the therapeutic potential of sulforaphane in mitigating kidney dysfunction in elders.